Effects of STEM Education Using Engineering Design Process on Problem Solving Ability of Elementary Students - Sasang, Suwimon; Klaimongkol, Yurawat (An Online Journal of Education, 2020)
The purposes of this research were 1) to compare the problem-solving ability of grade 3 students before and after the experiment was carried out with the experimental group 2) to compare the problem-solving ability of grade 3 students before and after the experiment was carried out with the control group, and 3) to compare differences in the abilities of the experimental group and the control group of grade 3 students to solve problems. The subjects were third grade students of a public school. There were 25 students in the experimental group and another 25 students in the control group. The research instruments were STEM educational activities using engineering design process, including questioning technique plans, and STEM educational activity using engineering plans. The data-collection instruments were the pre-test and post-test of problem-solving ability. The collected data were analyzed by mean, standard deviation, and t-test. The results of the study showed that 1) the problem-solving abilities of the students in the experimental group were higher than the students in the control group at a .05 level of significance; 2) the problem-solving abilities of the students in the experimental group were higher after the experiment at a .05 level of significance; and 3) the problem-solving abilities of students in the experiment group and the control group were not different